The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.51756/marlife.1073388
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of groundwater zooplankton fauna from water wells in Yayladağ district of Hatay province in Turkey

Abstract: Marine and Life SciencesSome water quality parameters (water temperature, conductivity and pH) and zooplankton fauna were investigated in 10 water wells. Fourteen ( 14) species of Rotifera (46.67%), 10 species of Copepoda (33.33%), and 6 species of Cladocera (20%) were recorded. It was observed that the most widely distributed species are Rotaria neptunia (7 wells), Keratella quadrata (5 wells), Daphnia curvirostris (8 wells), Coronatella rectangula (in 6 wells), Chydorus sphaericus and Pleuroxus aduncus (5 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…mehmetadami and K. xanthi, discovered in this study and recently added to the zooplankton fauna in inland waters of Turkey, were identified for the first time from interstitial samples from Turkey (Karaytuğ et al, 2018;Bruno and Cottarelli, 2015). K. xanthi was found for the second time in the Sarıseki stream and reeds (Bozkurt, 2017), and the third time in the well water in the Yayladağı district (Bozkurt, 2022). N. kosswigi and N. stammeri, which are rarely found in inland waters of Turkey, were found in the Dragon River (Bozkurt, 2017), additionally N. stammeri was found in the well waters of Yayladağ district (Bozkurt, 2022).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…mehmetadami and K. xanthi, discovered in this study and recently added to the zooplankton fauna in inland waters of Turkey, were identified for the first time from interstitial samples from Turkey (Karaytuğ et al, 2018;Bruno and Cottarelli, 2015). K. xanthi was found for the second time in the Sarıseki stream and reeds (Bozkurt, 2017), and the third time in the well water in the Yayladağı district (Bozkurt, 2022). N. kosswigi and N. stammeri, which are rarely found in inland waters of Turkey, were found in the Dragon River (Bozkurt, 2017), additionally N. stammeri was found in the well waters of Yayladağ district (Bozkurt, 2022).…”
Section: Discussionsupporting
confidence: 54%
“…Table 5. The relationships between zooplankton and water quality parameters was found in Turkey for the first time from Gölbaşı lake (Bozkurt, 2007), second time from Sarıseki stream (Bozkurt, 2017) and third time from Yayladağı well waters (Bozkurt, 2022). L. brevicornis was first reported from interstitial samples from Gölkent Lake in Turkey (Bozkurt, 2007).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Rotifera had the highest abundance with 16 taxa and 659 individuals; contributing 68.8% of the total zooplankton assemblage, followed by Copepoda -6 taxa and 228 individuals (23.8%) and Protozoa had 2 taxa and 71 individuals (7.4%). Rotifera had the highest abundance in line with Bozkurt (2019Bozkurt ( , 2022 especially in the uncovered wells (2, 4 and 5). This could be attributed to their capacity to tolerate wide range of physicochemical parameters (Hamaidi-Chergui et al, 2013).…”
Section: -Plankton Composition Abundance and Distributionmentioning
confidence: 98%
“…However, the overall abundance was high and comparable to some surfacewater environment in Nigeria. Elsewhere across the globe groundwater zooplankton were well documented (Cavite et al, 2017;Korbel et al, 2017;Bozkurt, 2019;Pociecha, et al, 2021;Bozkurt, 2022). Rotifera had the highest abundance with 16 taxa and 659 individuals; contributing 68.8% of the total zooplankton assemblage, followed by Copepoda -6 taxa and 228 individuals (23.8%) and Protozoa had 2 taxa and 71 individuals (7.4%).…”
Section: -Plankton Composition Abundance and Distributionmentioning
confidence: 99%